Penerapan Model Contextual Teaching and Learning untuk Meningkatkan Pemahaman Konsep Biologi Siswa - Amalia, Nurul (Biocaster : Jurnal Kajian Biologi, 2022)
Biology learning aims to develop critical thinking abilities and problem-solving skills, so that students can understand biological concepts, solve problems, and communicate solutions systematically. The aim of this research is to increase students' understanding of biological concepts through the application of contextual teaching and learning models. This type of research uses classroom action research which is carried out in two cycles. The subjects of this research were students in class XI MIA I SMA Negeri 5 Balikpapan, with a total of 32 students, consisting of 3 female students and 29 male students. The research instrument used was a test sheet. The data analysis technique used is quantitative. The results of the research showed that the test results evaluating students' understanding of biological concepts in cycle I had a classical completeness percentage of 45.14%. In cycle II, the test results evaluated students' understanding of biological concepts with a classical completeness percentage of 99%. There was an increase in the percentage of classical completeness by 53.86%. So it can be concluded that the contextual teaching and learning model has succeeded in increasing the understanding of biological concepts in class XI MIA I SMA Negeri 5 Balikpapan students.